2012
DOI: 10.1007/s11211-012-0152-0
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Regulation Hypothesis of Coping with an Unjust World: Ego-Depletion and Self-Affirmation as Underlying Aspects of Blaming of Innocent Victims

Abstract: People have a need to Belief in a Just World (BJW) in which people get what they deserve. When people are confronted with an event which threatens this BJW (e.g. when they witness a girl falling victim to rape), people try to maintain their existing beliefs, for example, by blaming the innocent victim for her ill fate. We argue that this defensive process of blaming innocent victims in essence stems from self-regulatory failure. In accordance with this line of reasoning, our first experiment shows that when se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
5
21
0
1
Order By: Relevance
“…Moreover, although we did not include an explicit manipulation check in our current studies, earlier studies did show that social proximity heightens a BJW threat (e.g., Bal & Van den Bos, 2010;Correaia et al, 2007). Moreover, our findings in the control condition of Study 1, showing that people blamed a proximal victim more than a distal victim, are in line with many earlier studies that included various other successful BJW threat manipulation (e.g., Hafer, 2000b, Loseman & Van den Bos, 2012Van den Bos & Maas, 2009;Van Prooijen & Van den Bos, 2009). Hence, we believe crime proximity to be a valid manipulation of BJW threat.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, although we did not include an explicit manipulation check in our current studies, earlier studies did show that social proximity heightens a BJW threat (e.g., Bal & Van den Bos, 2010;Correaia et al, 2007). Moreover, our findings in the control condition of Study 1, showing that people blamed a proximal victim more than a distal victim, are in line with many earlier studies that included various other successful BJW threat manipulation (e.g., Hafer, 2000b, Loseman & Van den Bos, 2012Van den Bos & Maas, 2009;Van Prooijen & Van den Bos, 2009). Hence, we believe crime proximity to be a valid manipulation of BJW threat.…”
Section: Discussionsupporting
confidence: 91%
“…We further propose that an other-focus will decrease derogatory reactions toward innocent victims and enhance helping of the victims involved. Consistent with earlier studies (e.g., , Hafer, 2000b, Loseman & Van den Bos, 2012Van den Bos & Maas, 2009;Van Prooijen & Van den Bos, 2009), we expect to find these effects especially following a high BJW threat. In these instances, people have a clear need to restore their BJW, whereas under a low BJW threat, reactions can be less pronounced (Hafer, 2000b).…”
Section: The Current Researchsupporting
confidence: 90%
See 1 more Smart Citation
“…For an enactor, holding the target of the harm-doing event responsible can result in outcomes such as feelings of anger and resentment toward that individual, and distancing when performing the harm-doing event (Loseman and van den Bos 2012). In terms of future interactions, when a negative event or behavior is attributed to a subordinate, abusive supervision may be the result (Lian et al 2014).…”
Section: Practical Implications For Enactors and Organizationsmentioning
confidence: 99%
“…From this perspective, initial, schema-based reactions to injustice may lead people to, for example, intuitively connect a random bad outcome to the recipient's prior bad deeds , have the impulse to punish perpetrators of harm (Goldberg, J. S. Lerner, & Tetlock, 1999), or spontaneously help a victim (Holmes, Miller, & Lerner, 2002;Rand, Greene, & Nowak, 2012). In support, a growing body of experimental research has suggested that people's reactions to victimization may occur intuitively-that is, without requiring a rational mind-set or much effortful thought (e.g., Aguiar, Vala, Correia, & Pereira, 2008;Callan, Ferguson, & Bindemann, 2013;Callan, Sutton, & Dovale, 2010;Goldberg et al, 1999;Loseman & van den Bos, 2012;Maas & van den Bos, 2009;van Prooijen & van de Veer, 2010). For example, adopting an eye-tracking methodology, Callan et al (2013) found that the good (bad) behavior of characters within audio-visual scenes biased participants' eye gaze towards images of good (bad) outcomes before the actual outcomes were revealed verbally.…”
Section: How Much Does Effortful Thinking Underlie Observers' Reactiomentioning
confidence: 99%